Competencies and training needs of agriculture extension officers in Rubber Industry Smallholders' Development Authority (RISDA), Department of Veterinary Services Malaysia (DVS) and Department of Agriculture Malaysia (DOA) - Zulkaflee, Nur Aziera (2015)
Agriculture sector has contribute to the growth and major contributor to national income and export earnings. Agriculture become important because it provide many job opportunities and food supply to people. Government also play active role in helping to develop agriculture industry in Malaysia. We need agriculture extension officers to educate farmers and people about the important of agriculture sector. The competency and training needs of Agriculture Extension Officers (AEO) in Malaysia is indeed one of the important determinants of success for agriculture industry in Malaysia. The general objective of this study is to identify the competency and training need of agriculture extension officers in DOA, DVS and RISDA. The specific objective is to identify the demographic profile of AEO, identify the training needs and competency level of AEO and examine the relationship between demographic profile and competency level. The questionnaire were distributed to 150 respondents. Respondents was selected among agriculture officers, agriculture assistant officer and agriculture assistant. Data were analyze using Statistical Package for Social Science (SPSS) for the descriptive, and ANOVA. The result show that competency level of DOA, RISDA and DVS were high in level, the trained preferences of the respondent also high in level. Based on ANOVA results it show that only competency in ICT have significance difference with demographic factor (age, level of education, level of position and years of working) while competency in planning, implementing, evaluating, communication, guiding and farm management show no significance difference. It can be concluded that the extension officers in these three department are well trained in this six type of dimension. Each department should focus more on ICT training to help extension officers master all the seven dimension of competency and extension agent should concentrate on improving where they are lacking.